The effect of pH in the adsorption of Alizarin and Eriochrome Blue Black R onto iron oxides - Pirillo, Silvina (2009)
The adsorption process of two dyes as a function of pH on three different adsorbents (goethite, Co-goethite, and magnetite) has been analyzed. Typical anionic adsorption behavior was observed for both dyes onto goethite and Co-goethite. The adsorption level was practically constant in the range of pH studied when the adsorbent was magnetite. The constant capacitance model (CCM) was employed to fit the experimental results. The surface complexes proposed from the adsorption data were in agreement with the patterns obtained from FTIR spectroscopy and a molecular mechanics calculation. Goethite has very good performance as adsorbent of Alizarin and Eriochrome Blue Black R. The presence of a foreign cation in Co-goethite does not improve the adsorption abilities of goethite. At low pH, the amounts of Alizarin and Eriochrome Blue Black R adsorbed on goethite and Co-goethite are similar. However, a higher dependence with the increase of pH is observed by Eriochrome Blue Black R. On magnetite, the dye adsorption shows less affinity for both dyes. Electronic and steric considerations can explain the trends found in the adsorption of the two dyes on the three iron oxides studied in this work. © 2009 Elsevier B.V. All rights reserved.